2017
DOI: 10.1111/ijn.12510
|View full text |Cite
|
Sign up to set email alerts
|

Urban‐rural disparity and determinants of delivery care utilization in Oromia region, Ethiopia: Community‐based cross‐sectional study

Abstract: Low delivery care utilization continues to be a public health problem that significantly contributes to maternal morbidity and mortality, especially in developing countries like Ethiopia. The aim of the study is to determine the extent of urban-rural disparity of delivery care utilization and its determinants. A community-based cross-sectional quantitative study supplemented with qualitative data was conducted from February 15 to March 10, 2014. Data were collected from eligible woman using interviewer-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
1
13
0
2
Order By: Relevance
“…Women from a rural residence were found to be less likely to have a delivery in a health facility. This finding is similar to those of previous studies conducted in Bangladesh and Indonesia ( Efendi et al, 2019 ; Kamal, 2013 ; Kenea & Jisha, 2017 ). Living in an urban residence allows easier access to health facilities than living in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Women from a rural residence were found to be less likely to have a delivery in a health facility. This finding is similar to those of previous studies conducted in Bangladesh and Indonesia ( Efendi et al, 2019 ; Kamal, 2013 ; Kenea & Jisha, 2017 ). Living in an urban residence allows easier access to health facilities than living in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Disparities of health services utilization related to rurality do not only happen in Indonesia. The research results with the focus of disparities in many countries reporting the disparities existing, among others in China (3)(9), Canada (10), The USA (11)(12), Ethiopia (13)(14), Mongolia (15), Australia (1), and Taiwan (16)(17). In addition to urban and rural, disparities in many countries also reportedly happened on many categories.…”
Section: Discussionmentioning
confidence: 99%
“…Women who live in urban areas prefer to deliver babies in healthcare facilities. An earlier study by Kenea and Jisha [22] in 2017 reported that delivery in healthcare facilities was dominated by urban mothers, while different studies found that mothers in rural areas preferred to deliver in nonhealthcare facilities or at home with traditional, yet noncertified, attendance [23, 24]. The accessibility and availability of facilities for childbirth could well be factors affecting the decision of where to deliver babies for both urban and rural mothers.…”
Section: Discussionmentioning
confidence: 99%